L’histoire de la géographie belge à travers les biographies nationales - Christian Vandermotten (Belgeo)
Four key periods characterise the history of Belgian geography: 1) between mid-16th and the beginning of the 17th Century, the glorious period of cartography of the Belgian principalties and the whole world, using informations provided by travellers and merchants; 2) after the independance, large scale cartography based on a precise geodesical survey (this period was already announced by Ferraris’ work at the end of the Austrian period; 3) the time of the Geographical Congresses and the foundation of the Geographical Societies, during the last quarter of the 19th Century, in the frame of the colonial project; 4) the quite late birth and growth of a true academic and scientific geography, not organised in the Belgian Universities before the first half of the 20th Century. These evolutions are enlighted through a systematic examination of the French and Dutch National Biographies.